Investigating EFL teachers' perceptions of task-based language teaching in higher education in China. Issue 2 (4th March 2021) - Liu, Yuying; Mishan, Freda; Chambers, Angela
ABSTRACT: While task-based language teaching (TBLT) is a teaching methodology favoured by the Chinese Ministry of Education, it has not been sufficiently researched to be validated empirically in practice in the EFL classroom. Few studies have investigated teachers' responses to TBLT in the Chinese college English context. This research contributes to addressing this gap by investigating EFL teachers' perceptions of TBLT and assessing the current implementation of TBLT. A mixed-method methodology was used with quantitative and qualitative data collected via questionnaires and interviews. The findings show that there is potential for the positive implementation of TBLT in the Chinese context. Most of the Chinese ELT teachers surveyed hold positive views on TBLT implementation and report a high frequency of using TBLT. However, this study also reveals that the majority of the participants are not confident in their understanding of TBLT, though they are willing to undergo training. In addition, the study found that the public examination system is seen as one of the key reasons that impede the implementation of TBLT. The article concludes with a discussion of practical implications of the findings of this small-scale study on how successful implementation of TBLT can be encouraged in the Chinese context.